The Effects of Creatine Monohydrate and/or Whey Protein on the Muscle Protein Synthesis and Anabolic Signaling Responses in Non-Stressed C2C12 Murine Myotubes - Nicholas J. Kontos; Joshua S. Godwin; Anthony Agyin-Birikorang; Darren G. Candow; Christopher M. Lockwood; Michael D. Roberts; Christopher B. Mobley (Physiologia)
Background/Objectives: Creatine monohydrate (CRE) is a popular nutritional supplement that increases lean/muscle mass accretion. Although data regarding CRE and its effects on muscle protein synthesis are mixed, we hypothesized that CRE may potentiate/extend the anabolic response to essential amino acids given that CRE acts as a high-energy phosphate buffer to potentially amplify anabolic signaling. Therefore, we used an in vitro model to determine whether CRE synergistically enhances myotube protein synthesis and the anabolic signaling responses to EAA-rich whey protein (WP). Methods: C2C12 murine myotubes were treated with control media containing PBS (CTL), WP serum (5 mg/mL), CRE (10 mM), or WP + CRE. Myotubes were collected following 1, 4, and 24 h treatments (n = 6 replicates per treatment and time point) and assayed for relative creatine levels, myotube protein synthesis levels, and phosphorylation markers. Results: Cellular creatine levels were greater in CRE and WP + CRE versus CTL and WP at all treatment time points (p < 0.05). The protein synthesis levels with 4 hr treatments with WP and WP + CRE were greater compared to the CTL (p = 0.036 and p < 0.001, respectively), and 24 h levels were greater with WP versus other treatments (p < 0.05). p-p70S6K (Ser389) and p-rpS6 (Ser235/236) were greater with WP at 1 h compared to all other treatments (p < 0.05). No effects across time points were observed for p-mTOR (Ser2448), p-4E-BP1 (Thr37/46), or p-AMPKα (Thr172). Conclusions: WP increases protein synthesis and anabolic signaling with no additive effect from CRE. However, given that myotubes were not stressed nor stimulated to contract, such models are needed with the current treatment schematic to examine potential interactions.